2020
DOI: 10.3390/ijms21124324
|View full text |Cite
|
Sign up to set email alerts
|

Purified Tea (Camellia sinensis (L.) Kuntze) Flower Saponins Induce the p53-Dependent Intrinsic Apoptosis of Cisplatin-Resistant Ovarian Cancer Cells

Abstract: Ovarian cancer is currently ranked at fifth in cancer deaths among women. Patients who have undergone cisplatin-based chemotherapy can experience adverse effects or become resistant to treatment, which is a major impediment for ovarian cancer treatment. Natural products from plants have drawn great attention in the fight against cancer recently. In this trial, purified tea (Camellia sinensis (L.) Kuntze) flower saponins (PTFSs), whose main components are Chakasaponin I and Chakasaponin IV, inhibited the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…A few examples of saponins with biological importance include ginsenoside RK1, panax notoginsen, panax quinquefolius, and paris saponin-II [156][157][158]. In addition, saponins collected from flowers, such as Camellia sinensis, appear to sensitize cisplatin-resistant cells by inducing apoptosis in certain ovarian cancers [159,160]. A synergistic effect of saponins, such as β-elemene (Rhizoma zedoariae) and from medicago species, has been observed in cervical and breast cancer when treated in combination with cisplatin [161,162].…”
Section: Combination With Saponinsmentioning
confidence: 99%
“…A few examples of saponins with biological importance include ginsenoside RK1, panax notoginsen, panax quinquefolius, and paris saponin-II [156][157][158]. In addition, saponins collected from flowers, such as Camellia sinensis, appear to sensitize cisplatin-resistant cells by inducing apoptosis in certain ovarian cancers [159,160]. A synergistic effect of saponins, such as β-elemene (Rhizoma zedoariae) and from medicago species, has been observed in cervical and breast cancer when treated in combination with cisplatin [161,162].…”
Section: Combination With Saponinsmentioning
confidence: 99%
“…Green tea ( C. sinensis ) contains many bioactive compounds, including catechins, caffeine, saponins, theanine, vitamins, mineral oil, and trace elements [ 51 , 52 ]. Green tea components have many biological and biochemical effects, including antimutation [ 53 ], anticarcinogenesis [ 54 ], antioxidation [ 55 ], apoptosis-inducing [ 41 ], and antiangiogenesis effects. Major bioactive compounds present in green tea seeds include flavonoids, EGCG, saponin glycosides, kaempferol, and naringenin [ 56 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that saponins can protect against nephrotoxicity induced by cisplatin. Saponins cause cell resistance because cisplatin becomes sensitized by inducing apoptosis in ovarian cancer 36 . The synergistic increase in cytotoxic effect that occurs in the combination of HSE and cisplatin needs to be investigated further.…”
Section: Inhibition Of Cell Proliferation Testmentioning
confidence: 99%